A cross-linguistic perspective as a starting point for conceptual grammar teaching in school language subjects - Hagemann, Kristin; Søfteland, Åshild (Acta Didactica Norden, 2023)
In this article, we seek to connect the most recent research within L1, L2 and L3 grammar teaching, aiming at creating a common ground for the ongoing debate concerning what grammar teaching in the Norwegian school should be, and where and how it should take place. We show that research on grammatical threshold concepts and meta concepts make a good starting point for increasing the collaboration between the school language subjects, and that the teaching of foreign languages (L3) and English (L2) may contribute to consolidating parts of the Norwegian subject content. Grammar teaching provides a context where it is both simple and effective to make use of the students’ multilingualism, and we argue that the recent attention to conceptual grammar teaching in the L1 research actualizes the idea of a systematic, cross-linguistic grammar teaching in school.